Artemisinin: A Case Study in the Evolution of Synthetic Strategy - Cook, Silas P. (Synlett, 2014)
Artemisinin represents one of the most important discoveries in the fight against malaria over the last 50 years. As the first endoperoxide-containing natural product, artemisinin has attracted chemists and biologists alike with its potent activity and rapid onset against malaria-causing Plasmodium species. Since its disclosure in 1979, artemisinin has been the subject of several elegant syntheses. Herein, the evolution of synthetic strategy is discussed in the context of artemisinin.
Keywords: terpenoids; total synthesis; malaria; natural products; endoperoxide